Food supply: consumers and their expectations - Sylvan, Louise (Acta Bioethica, 2001)
In a century of significant improvements in health for many in the world, the last thing consumers expected at the close of this millennium was that the old problems of food safety would be intensified due to the introduction of new methods and technologies in the agri-business domain. Consumers and citizens have often reacted angrily at the risk that governments and experts have been willing to expose them to. While presented as decisions based solely on science, many of the decisions taken about food safety and food trade, at national and international levels, have a significant ethical element - most of the times unidentified and/or ignored.